2021
DOI: 10.3390/antiox10020149
|View full text |Cite
|
Sign up to set email alerts
|

Urban Aerosol Particulate Matter Promotes Necrosis and Autophagy via Reactive Oxygen Species-Mediated Cellular Disorders that Are Accompanied by Cell Cycle Arrest in Retinal Pigment Epithelial Cells

Abstract: Urban particulate matter (UPM) is recognized as a grave public health problem worldwide. Although a few studies have linked UPM to ocular surface diseases, few studies have reported on retinal dysfunction. Thus, the aim of the present study was to evaluate the influence of UPM on the retina and identify the main mechanism of UPM toxicity. In this study, we found that UPM significantly induced cytotoxicity with morphological changes in ARPE-19 human retinal pigment epithelial (RPE) cells and increased necrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Furthermore, Chua et al [ 57 ] reported that subjects exposed to higher levels of PM 2.5 were associated with changes in retinal structure features, including RCG and IPL thickness. Previously, we suggested that PM 2.5 mediates retinal dysfunction through ROS-mediated epithelial-mesenchymal transition and necrotic and autophagic cell death in retinal pigment epithelial cells [ 64 , 65 ]. Additionally, our current findings showed that topical exposure to PM 2.5 led to the loss of retinal ganglion cells and the decrease of the NFL/GCL+IPL thickness; however, spermidine eye drops contribute to the normalization of retinal ganglion cell density and retinal structure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Chua et al [ 57 ] reported that subjects exposed to higher levels of PM 2.5 were associated with changes in retinal structure features, including RCG and IPL thickness. Previously, we suggested that PM 2.5 mediates retinal dysfunction through ROS-mediated epithelial-mesenchymal transition and necrotic and autophagic cell death in retinal pigment epithelial cells [ 64 , 65 ]. Additionally, our current findings showed that topical exposure to PM 2.5 led to the loss of retinal ganglion cells and the decrease of the NFL/GCL+IPL thickness; however, spermidine eye drops contribute to the normalization of retinal ganglion cell density and retinal structure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a correlation between PM 2.5 and changes in retinal structure features in subjects exposed to higher levels of PM 2.5 was reported [ 59 ]. Previously, we suggested that PM 2.5 mediates retinal dysfunction through ROS-mediated epithelial–mesenchymal transition and necrotic and autophagic cell death in retinal pigment epithelial cells [ 62 , 63 ]. Our present findings showed that topical exposure to PM 2.5 led to the loss of retinal ganglion cells and the decrease of the NFL/GCL + IPL thickness; however, oral administration of CFW contributed to the normalization of retinal ganglion cell density and retinal constitution.…”
Section: Discussionmentioning
confidence: 99%
“…After the indicated treatment, the cells were fixed with 4% paraformaldehyde, permeabilized in 0.5% Triton X-100 and then blocked with 2% bovine serum albumin (Sigma-Aldrich Chemical Co.) as described previously ( Lee et al, 2021 ). Subsequently, the cells were probed with anti-p-Nrf2 antibody (Ser 139) at 4°C overnight and then washes with ice-cold PBS.…”
Section: Materials and Methdsmentioning
confidence: 99%